Entrepreneurial behavior: Impact of motivation factors on decision to create a new venture - Virginia Barba-Sánchez; Carlos Atienza-Sahuquillo (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2012)
Newly created enterprises increase the dynamism of economies and generate employment. Thus, they are the object of growing research interest. Forming a new company represents a decision based on both personal and subjective motives, as well as on the environment. But regardless of the origin, a founder's motivation represents a commitment to a project or business idea, and thus dictates the future success of the enterprise. This article investigates the motivational profiles of entrepreneurs, and why they choose to create new industrial enterprises. To detail this profile, we present the results of an empirical study of 101 entrepreneurs who have founded companies. The results offer significant conclusions for both academics and practitioners. Firstly, making money or being one's own boss does not appear to be sufficient reasons to create a new venture. Secondly, the motivation content of entrepreneurs influences their decision to start a business. From these conclusions, some relevant guidelines are suggested.
Keywords: L26; M13; 650; entrepreneurship; entrepreneurial motivation; entrepreneurial decision making